Effects of various toothpastes on remineralization of white spot lesions - Jo, Su-Yeon (Korean Association of Orthodontists, 2014)
OBJECTIVE: The purpose of this in vitro study was to examine the effects of fluoridated, casein phosphopeptide.amorphous calcium phosphate complex (CPP-ACP)-containing, and functionalized β-tricalcium phosphate (fTCP)-containing toothpastes on remineralization of white spot lesions (WSLs) by using Quantitative light-induced fluorescence (QLF-D) Biluminator™ 2. METHODS: Forty-eight premolars, extracted for orthodontic reasons from 12 patients, with artificially induced WSLs were randomly and equally assigned to four treatment groups: fluoride (1,000 ppm), CPP-ACP, fTCP (with sodium fluoride), and control (deionized water) groups. Specimens were treated twice daily for 2 weeks and stored in saliva solution (1:1 mixture of artificial and human stimulated saliva) otherwise. QLF-D Biluminator™ 2 was used to measure changes in fluorescence, indicating alterations in the mineral contents of the WSLs, immediately before and after the 2 weeks of treatment. RESULTS: Fluorescence greatly increased in the fTCP and CPP-ACP groups compared with the fluoride and control groups, which did not show significant differences. CONCLUSIONS: fTCP- and CPP-ACP-containing toothpastes seem to be more effective in reducing WSLs than 1,000-ppm fluoride-containing toothpastes.